Penguatan Iman yang Tawar melaui Narasi Kemesiasan Yesus dalam Lukas 24:13-49 - Jefrie Walean (Jurnal EFATA: Jurnal Teologi dan Pelayanan, 2021)
The structure of Luke 24 is part of an additional dialogue between Jesus and two of His disciples who were on their way to Emmaus. the content of the Jesus dialogue is a Christian theological framework that is strong enough to reaffirm the state of the Christian faith which is full of doubts. This research is qualitative research that uses a descriptive method to obtain a theoretical structure in compiling an essential description of Christian theology. It is concluded that the fact of Jesus' resurrection in the dialogue is evidence that Jesus' messiahship strengthens the bargaining position of the Christian faith in apologizing. AbstrakStruktur Lukas 24 merupakan bagian dialog tambahan antara Yesus dengan dua orang murid-Nya yang sedang dalam perjalanan ke Emaus. Isi dialog Yesus adalah kerangka teologis Kristen yang cukup kuat menguatkan kembali keadaan tawar iman Kristen. Penelitian ini merupakan penelitian kualitatif yang menggunakan metode deskriptif untuk mendapatan susunan teoretis dalam menyusun uraian teologi Kristen yang esensial. Disimpulkan bahwa, fakta ke-bangkitan Yesus dalam dialog tersebut menjadi bukti bahwa kemesiasan Yesus memperkuat keadaan tawar iman Kristen dalam berapologet.